2002
DOI: 10.1289/ehp.02110543
|View full text |Cite
|
Sign up to set email alerts
|

Indoor dampness and molds and development of adult-onset asthma: a population-based incident case-control study.

Abstract: Previous cross-sectional and prevalent case-control studies have suggested increased risk of asthma in adults related to dampness problems and molds in homes. We conducted a population-based incident case-control study to assess the effects of indoor dampness problems and molds at work and at home on development of asthma in adults. We recruited systematically all new cases of asthma during a 2.5-year study period (1997-2000) and randomly selected controls from a source population consisting of adults 21-63 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 29 publications
5
115
1
Order By: Relevance
“…An increased risk of asthma in professions not normally associated with OA has led to the suspicion that proteins derived from ubiquitous agents may be responsible. Moulds in water-damaged buildings have been suggested as an explanation for an increased risk of asthma among educators [71], confirming two other recent reports [72,73].…”
Section: Asthma Attributable To Work Exposuressupporting
confidence: 81%
“…An increased risk of asthma in professions not normally associated with OA has led to the suspicion that proteins derived from ubiquitous agents may be responsible. Moulds in water-damaged buildings have been suggested as an explanation for an increased risk of asthma among educators [71], confirming two other recent reports [72,73].…”
Section: Asthma Attributable To Work Exposuressupporting
confidence: 81%
“…Waegemaekers et al 22 assessed the risk of asthma related to residential dampness stratified by sex and found a greater risk in women (OR: 4.16) than in men (OR: 1.15), which was consistent with our result. A recent case-control study in Finland 23 found a relatively stronger effect between workplace mold and asthma development in women (OR: 1.67) than in men (OR: 1.26). A cohort study of schoolchildren in Japan 24 found a significant association between the prevalence of respiratory symptoms and indoor nitrogen dioxide in girls but not in boys.…”
Section: E392mentioning
confidence: 96%
“…The program controls the interview logic, branching to or skipping questions as needed according to the responses of the interviewee, and it validates the logic of the data as they are entered. The exposure part of the questionnaire was designed specifically for this study, while the part on respiratory symptoms and diseases was modified from the questionnaire used in the Finnish Environment and Asthma Study that was originally designed for studying general population samples (8,(21)(22)(23). The questionnaire inquired about personal characteristics, occupational history, use of chemicals and other agents, job tasks, preventive measures, smoking, and the occurrence of upper and lower respiratory symptoms, asthma, skin symptoms, and some general symptoms.…”
Section: Questionnairementioning
confidence: 99%